Urban Sprawl Modeling using RS and GIS Technique in Kirtipur Municipality (Journal on Geoinformatics, Nepal, 2013)
Urban sprawl refers to the urbanization extent, which is mainly caused by population growth and large scale migration and it is a global phenomenon. In developing countries like Nepal, where the population growth and internal migration rate in urban area is high, it has posed serious implication on the resources of the region. Effective and efficient infrastructure planning of an urban environment require information related to the rate of urban growth along with its trend, pattern and extent of urban sprawl. The pattern and extent of urban sprawl is identified and modeled using remotely sensed data along with collateral data. RS and GIS are used to analyze and interpret the urban land use changes. Cellular Automate Markov (CA-Markov) process is used to urban sprawl modeling to identify possible pattern of sprawl and subsequently predict the nature of future sprawl Nepalese Journal on Geoinformatics -12, 2070 (2013AD): 50-56